The Role of Education in Humanization - Freire, Paulo (Critical Education, 2026)
This text is a summary of lectures given by Paulo Freire at a conference held in Santiago in May 1967, under the sponsorship of the Organization of American States, the government of Chile, and the University of Chile. Translated from the version published in the FAEEBA Journal – Education and Contemporary Studies, n°. 7, January/July 1997, this paper condenses the ontological and epistemological foundations of the Brazilian educator, as well as demonstrating his more direct relationship with phenomenology and existentialism through direct appropriation of Gabriel Marcel, Jean-Paul Sartre, Karl Jaspers and a vast phenomenological vocabulary.